Optimalisasi Desain PLTS Hybrid Untuk Efisiensi Energi Pada Gedung Teknologi Rekayasa Energi Terbarukan - Ruswandi Djalal, Muhammad; Marhatang, Marhatang; Syahimullah, Akzar Dwi; Ardiansya Syamsul, Vito (Jurnal Teknik Mesin Sinergi, 2025)
The increasing demand for electrical energy necessitates the implementation of sustainable and efficient renewable energy technologies. This study aims to design and evaluate the performance of a Hybrid Solar Photovoltaic (PV) System integrated with the Internet of Things (IoT) at the Renewable Energy Engineering Technology (TRET) Building of Politeknik Negeri Ujung Pandang. The system combines energy from solar panels, batteries, and the utility grid, supported by an IoT-based monitoring platform for real-time observation of electrical parameters. The research methodology includes hardware configuration using PV modules, a hybrid inverter, battery storage, PZEM-004T and PZEM-017 sensors, and an ESP32 microcontroller connected to the Blynk application. Performance testing was conducted by measuring voltage, current, power, energy, and solar irradiation, as well as calculating daily irradiation, specific yield (Yf), performance ratio (PR), panel efficiency, and overall system efficiency. The experimental results indicate that the hybrid PV system operates efficiently and reliably, achieving a daily solar irradiation of 6.37 kWh/m², a specific yield of 7.92 kWh/kWp, and a performance ratio of 124.3%. The average panel efficiency reached 12.1%, while the system efficiency was 23.5%. Meanwhile, the on-grid system achieved a panel efficiency of 27.9%, system efficiency of 27.7%, and a PR of 146.5%, whereas the off-grid configuration yielded a panel efficiency of 13.6%, system efficiency of 14.6%, and a PR of 77.3%. These findings demonstrate that the hybrid configuration effectively integrates the strengths of both on-grid and off-grid systems, resulting in optimal performance. Additionally, IoT integration enhances monitoring and control capabilities, supporting efficient energy usage and enabling smart renewable energy management. Thus, the IoT-enabled hybrid PV system proves effective in promoting energy efficiency and serves as a model for sustainable renewable energy implementation.